APPROXIMATION OF INTERFACIAL TENSION FOR ASPHALTENIC CRUDE OIL AND CO2 USING PARACHOR METHOD - AHMAD NAZRI, MOHAMMAD IFFWAD (2011)
In this study, new way to handle the determination of interfacial tension for asphaltenic crude oil and CO2 using parachor method is proposed. Parachor is one empirical method that can be use to predict interfacial tension and is widely used in the industry. Parachor method is dependent on the phase density, molecular weight, parachor value for each components and the scaling exponent. Earlier study defined the value of scaling exponent to be 3.67, 3.88,3.91 and 4.00. However, these proposed values are not design to predict the IFT for crude oil that contain asphaltenes contain more than 0.01%. As a result, the predicted IFT will yield an error when comparing the results with the laboratory determination. This paper will use four types of asphaltenic crude oil that contain different percentage of asphalt. The samples are Dulang Crude Oil, Iraq Ratawi Crude Oil, and mixture of 80% Dulang Crude and 20% Iraq Ratawi Crude, and 20% Dulang Crude and 80% Iraq Ratawi Crude. To compare the empirical method, this project will implement IFT pendant drop experiment as the main laboratory work. Analysis of this data comparison will leads to a new scaling exponent value that will yield an accurate interfacial tension for asphaltenic crude oil.